Pengembangan Usaha Usus Krispy Melalui Identitas Merek (Brand Identity) Dan Digital Marketing Pada UMKM Usus Krispy Dusun Sandongan Timur Desa Saribaye Kecamatan Lingsar, Lombok Barat - Nizar Hamdi; Zulkarnaen; Sofiati Wardah; Baiq Desthania Prathama; Galuh Ratna Mutia (Valid Jurnal Pengabdian, 2026)
This community service initiative aims to develop the MSME sector in Sari Baye Village, Lingsar District, West Lombok Regency. One of the micro-enterprises selected for assistance is a home-based "Crispy Chicken Intestine" business located in Sandongan Timur Hamlet, Sari Baye Village, Lingsar District; this is a locally-owned culinary micro-enterprise known for its distinctive taste and affordable pricing. Chicken intestines—often viewed as a mundane food ingredient—can be processed into a crispy, savoury snack with higher market value. The Crispy Chicken Intestine product also offers development potential through various flavour variants, such as original, *balado* (spicy chilli), hot/spicy, barbecue, and cheese. Such variety can enhance product appeal and reach broader market segments, ranging from children and teenagers to adults. The business owner faces challenges regarding the lack of an attractive brand identity and the absence of digital marketing efforts via the internet or social media. Sales currently rely on consignment at small kiosks, and the product is not yet widely known within the Lingsar District community. To address these issues, the community service team provided business development assistance through the following measures: 1) Conducting outreach on the importance of an attractive brand identity and product promotion via digital marketing; 2) Providing training and guidance on brand identity design; and 3) Providing training and guidance on designing promotional materials for digital marketing.